Postbiotic Lactiplantibacillus plantarum CECT 9161 Influences the Canine Oral Metagenome and Reduces Plaque Biofilm Formation - Adrián Florit-Ruiz; Laura Rago; Antonia Rojas; Bellahanum Guzelkhanova; Adrià Pont-Beltran; Araceli Lamelas; María Carmen Solaz-Fuster; Juan F. Martinez-Blanch; María Enrique López; Guillermo García-Lainez; Bob T. Rosier; Richard Day; et al. (Animals)
Periodontal diseases are highly prevalent in dogs and intricately interconnected with the composition and functional attributes of the oral microbiota. The demand for non-invasive interventions to support oral health presents an opportunity for functional ingredients. The novel postbiotic heat-treated (HT) Lactiplantibacillus plantarum CECT 9161 inhibited growth and biofilm formation of oral microorganisms in vitro. The in vitro growth of saliva-derived biofilms was also inhibited and revealed microbiome modulation. Two doses of the postbiotic (LOW: 5 mg dog/day, HIGH: 25 mg/dog/day) were assessed in a placebo-controlled, double-blinded, 57-day clinical trial involving 60 dogs. Associations were found between the postbiotic, reduced plaque formation, and modulation of the oral microbiome, including increased abundance of genes involved in denitrification, heme and catechol biosynthesis, and oxidative stress reduction. The results suggest that HT Lactiplantibacillus plantarum CECT 9161 may support oral health in dogs by modifying the microbiome of supragingival plaque and reducing plaque formation.